Enhanced metabolic versatility of planktonic sulfur-oxidizing γ-proteobacteria in an oxygen-deficient coastal ecosystem - Murillo, Alejandro A.; Ramírez-Flandes, Salvador; DeLong, Edward F.; Ulloa, Osvaldo (Frontiers in Marine Science, 2014)
Sulfur-oxidizing Gamma-proteobacteria are abundant in marine oxygen-deficient waters, and appear to play a key role in a previously unrecognized cryptic sulfur cycle. Metagenomic analyses of members of the uncultured SUP05 lineage in the Canadian seasonally anoxic fjord Saanich Inlet (SI), hydrothermal plumes in the Guaymas Basin (GB) and single cell genomics analysis of two ARCTIC96BD-19 representatives from the South Atlantic Sub-Tropical Gyre (SASG) have shown them to be metabolically versatile. However, SI and GB SUP05 bacteria seem to be obligate chemolithoautotrophs, whereas ARCTIC96BD-19 has the genetic potential for aerobic respiration. Here, we present results of a metagenomic analysis of sulfur-oxidizing Gamma-proteobacteria (GSO), closely related to the SUP05/ARCTIC96BD-19 clade, from a coastal ecosystem in the eastern South Pacific (ESP). This ecosystem experiences seasonal anoxia and accumulation of nitrite and ammonium at depth, with a corresponding increase in the abundance of GSO representatives. The ESP-GSOs appear to have a significantly different gene complement than those from Saanich Inlet, Guaymas Basin and SASG. Genomic analyses of de novo assembled contigs indicate the presence of a complete aerobic respiratory complex based on the cytochrome bc1 oxidase. Furthermore, they appear to encode a complete TCA cycle and several transporters for dissolved organic carbon species, suggesting a mixotrophic lifestyle. Thus, the success of sulfur-oxidizing Gamma-proteobacteria in oxygen-deficient marine ecosystems appears due not only to their previously recognized anaerobic metabolic versatility, but also to their capacity to function under aerobic conditions using different carbon sources. Finally, members of ESP-GSO cluster also have the genetic potential for reducing nitrate to ammonium based on the nirBD genes, and may therefore facilitate a tighter coupling of the nitrogen and sulfur cycles in oxygen-deficient waters.